Patterns of Long Term Growth in Sub-Saharan Africa - Arbache, Jorge Saba; Page, John (World Bank, Washington, DC, 2012)
Using the most recent purchasing power parity data for 44 sub-Saharan African countries, this paper examines the characteristics of long run growth in Africa between 1975 and 2005. The authors investigate the following issues: cross-country income structure, income convergence, the country level distribution of income, growth and income persistence, and formation of convergence clubs.